Suitability of photovoltaic development and emission reduction benefits based on geographic information sensing and multi-criteria decision making method—an example from Inner Mongolia Autonomous Region - Xu, Wei; Liu, Zhenling; Liu, Susu (Frontiers in Energy Research, 2023)
With the rapid development of the photovoltaic (PV) industry, the problem of the blind construction of PV power plants is becoming increasingly prominent. Thus, the scientific evaluation of the suitability of regional PV products, power generation potential, and emission reduction benefits is of great significance to the sustainable development of the PV industry. In this study, geographic information sensing and multi-criteria decision making methods are to be combined to calculate a PV development suitability index based on meteorology, topography, location, and vegetation to characterize the spatial patterns of the PV development in the Inner Mongolia Autonomous Region.Subsequently, the power generation potential and emission reduction benefits under different development scenarios were quantitatively assessed. The particularly suitable, and more suitable areas for the PV development in the Inner Mongolia Autonomous Region are 23.66% of the total area. Among these, the more suitable areas are the most extensive. The suitability of PV development in the western part of the Inner Mongolia Autonomous Region is more than that in the central and eastern parts. The suitable areas are mainly distributed in the Alashan League and Bayannur City in the west. Thus, the Inner Mongolia Autonomous Region has enormous potential for electricity generation. The development of 12.57% of the particularly suitable areas can meet the electricity consumption of the Inner Mongolia Autonomous Region in 2021. Moreover, sensitivity analysis is conducted to investigate the impacts of system efficiency variation on energy output. The distribution of the power generation potential and electricity demand in the Inner Mongolia Autonomous Region has robust spatial heterogeneity. PV power generation can achieve remarkable energy saving and emission reduction. If all particularly suitable areas are developed, the annual carbon emission reduction of the Inner Mongolia Autonomous Region will be approximately 2,446,621,000 t, which is 4.46 times the total carbon emission of the Autonomous Region and 21.2% of the total carbon emission of China in 2021. Therefore, this study provides a scientific reference and guide for selecting suitable sites for PV power plants and their sustainable development in the Inner Mongolia Autonomous Region.